A novel method for the spectrophotometric determination of nitrite in water - (:unkn) unknown (ELSEVIER, 2005)
A rapid, simple, selective and sensitive method for the spectrophotometric determination of nitrite in water has been developed and optimum reaction conditions along with other analytical parameters have been evaluated. Nitrite reacts with barbituric acid in acidic solution to give the nitroso derivative, violuric acid. At analytical wavelength of 3 10 nm, Beer's law is obeyed over the concentration range 0.00-3.22 ppm of nitrite. The molar absorptivity is 15330 +/- 259.7 (95%) with pooled standard deviation of 355.57 and R.S.D. of 2.32%. As well as the method is sensitive (2.99 x 10(-3) mu g NO2 cm(-2)) and selective, it tolerates most of the potential interferents. It has been successfully applied to nitrite determination in natural waters by use of a calibration graph with determination limit of 1.66 mu g NO2 in 100 mL working solution corresponding to minimum 9.5 ppb NO2-N in water samples. Lower concentrations of nitrite (3.0 mu g NO2/L sample) is precisely analyzed by using the method of dilution with sample, with R.S.D. of lower than 0.5%. The results were compared with standard N-(1-naphtyl)ethylenediamine dihydrochloride method and very good agreement between the data was observed. The method can easily be applied in the field. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: nitrite determination; barbituric acid; nitrite in water; spectrophotometry; NITROGEN-DIOXIDE; PHOTOMETRIC-DETERMINATION; COUPLING AGENT; NITRATE; ION; DIAZOTIZATION; PRECONCENTRATION; EXTRACTION; ELECTRODES; REAGENT